2005
DOI: 10.1021/ja0568244
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical Evaluation of Alternating Duplex−Triplex Conversion Effect on the Anthraquinone-Photoinjected Hole Transport through DNA Duplex Immobilized on a Gold Electrode

Abstract: Amperometry was employed to characterize the anthraquinone (AQ)-photoinjected hole transport through a 20-mer oligodeoxynucleotide (ODN) duplex, as immobilized on the surface of a gold electrode, and its triplex forms converted by association with several third oligopyrimidine (OPD) short strands. While the cathodic photocurrent was observed upon irradiation at 365 nm of the AQ photosensitizer linked to the end of DNA duplex, a marked lowering of the current density was identified to occur by the triplex forma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
29
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 18 publications
2
29
0
Order By: Relevance
“…[28] Coupling of Nhydroxysuccinimidyl ester 1 with ODN N gave the desired ODN F1. [29,30] The crude ODN F1 was purified by reversed phase HPLC and the incorporation of d F1 U was confirmed by enzymatic digestion and ESI-TOF mass spectrometry.…”
Section: Resultsmentioning
confidence: 99%
“…[28] Coupling of Nhydroxysuccinimidyl ester 1 with ODN N gave the desired ODN F1. [29,30] The crude ODN F1 was purified by reversed phase HPLC and the incorporation of d F1 U was confirmed by enzymatic digestion and ESI-TOF mass spectrometry.…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, we confirmed that cleavage at the GG 6 site in Duplex II increased at 20 ˚C (lanes 3) because of the temperature effect on long-range hole transport through the DNA duplex, consistent with previous reports. 34,35,41 These results suggest that the hole injected from the AQ chromophore in Triplex II at 20 ˚C could arrive at the GG 5 sites as a result of the dissociation of ODN 8, whereas hole transport between the GG 5 and GG 6 sites was still suppressed by the binding of ODN 7 to form a partial triplex. Further raising the reaction temperature to 40 ˚C increased DNA cleavage at the GG 6 site in Triplex II (lane 9 in Figure 5A and…”
Section: Resultsmentioning
confidence: 88%
“…[27][28][29][30] Furthermore, experiments on the oxidative cleavage of DNA and the photocurrent measurement of DNA on a gold electrode showed that a DNA triplex region involving a pyrimidine·purine·pyrimidine motif, such as C + ·GC, has a lower hole transport capability because of its cationic environment and dissonant stacking interactions at the duplex-triplex junctions. [31][32][33][34][35] Following on from these researches on hole transport properties of DNA triplex, we constructed a regulation system of hole transport in DNA by regulating the formation and dissociation of triplex. Figure 1A illustrates the concept of the regulation system, in which hole transport in an anthraquinone (AQ)-tethered duplex 36 is regulated by the thermally-reversible association and dissociation of a short-strand oligodeoxynucleotide (ODN) with duplex DNA to form the triplex.…”
Section: Introductionmentioning
confidence: 99%
“…[12,13] Nevertheless, there are only a few reports concerning DNA-based photoelectrochemical devices. [14][15][16] In particular, a fundamental understanding of the photocurrent generation through DNA films has not been developed, which is essential for the further development of such a device. Herein, we describe how important the relative rates of charge recombination and charge transfer are for the efficient photocurrent generation through DNA films and show the effect of a single base mismatch on the photocurrent efficiency.…”
mentioning
confidence: 98%